2006
DOI: 10.1007/s00213-006-0362-y
|View full text |Cite
|
Sign up to set email alerts
|

Anxiogenic and aversive effects of corticotropin-releasing factor (CRF) in the bed nucleus of the stria terminalis in the rat: role of CRF receptor subtypes

Abstract: Rationale-Corticotropin releasing factor (CRF) produces anxiety-like and aversive effects when infused directly into the various regions of the brain, including the bed nucleus of the stria terminalis (BNST). However, the CRF receptor subtypes within the BNST mediating these phenomena have not been established.Objectives-We used selective CRF receptor antagonists to determine the receptor subtypes involved in the anxiogenic-like and aversive effects CRF in the BNST. Methods-MaleLong-Evans rats were bilaterally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(150 citation statements)
references
References 94 publications
7
137
2
4
Order By: Relevance
“…Using specific CRF 1 and CRF 2 receptor antagonists, we found circumstantial evidence for both converging and opposing receptor functions, dependent on the behavior under investigation. Although our results support previous reports of CRF receptor function on the anxiety-like behavior in the EPM (Sahuque et al, 2006;Sink et al, 2013) and modulation of somatic pain processing (Ji and Neugebauer, 2008), the observed changes in visceral sensitivity contradicted previous studies using peripherally restricted CRF 1 and CRF 2 receptor antagonists (Greenwood- Nijsen et al, 2005). This suggested that the effects of CRF 1 and CRF 2 receptor activation, at least on visceral sensitivity, may differ depending on the localization of the receptors.…”
Section: The Effect Of Was On Crf Mechanisms In the Bnst Alcontrasting
confidence: 51%
“…Using specific CRF 1 and CRF 2 receptor antagonists, we found circumstantial evidence for both converging and opposing receptor functions, dependent on the behavior under investigation. Although our results support previous reports of CRF receptor function on the anxiety-like behavior in the EPM (Sahuque et al, 2006;Sink et al, 2013) and modulation of somatic pain processing (Ji and Neugebauer, 2008), the observed changes in visceral sensitivity contradicted previous studies using peripherally restricted CRF 1 and CRF 2 receptor antagonists (Greenwood- Nijsen et al, 2005). This suggested that the effects of CRF 1 and CRF 2 receptor activation, at least on visceral sensitivity, may differ depending on the localization of the receptors.…”
Section: The Effect Of Was On Crf Mechanisms In the Bnst Alcontrasting
confidence: 51%
“…For instance, priming of the BNSTinduced anxiety-like behavior in SI test without affecting performance in EPM. Considering that the intra-BNST CRF system has been implicated in anxiety responses measured in EPM (Sahuque et al, 2006), the lack of changes in EPM measure in the current study is intriguing. One possible explanation is that CRF injections into the BNST were given bilaterally in the study by Sahuque et al, where as in the present study, priming was done with unilateral injections.…”
Section: Discussionmentioning
confidence: 79%
“…results of Sahuque et al, 2006, demonstrating that the anxiogenic effects of CRF in the BNST was mediated by CRF1 receptors, where as the stress-induced reinstatement of drug-seeking behavior was mediated by both CRF1 and CRF2 receptors.…”
Section: Discussionmentioning
confidence: 93%
“…It was surprising that a higher dose of CRH had no substantial effect on EPM behavior, but the lower dose did. CRH generally produces dose-dependent increases in anxietyrelated behaviors when microinjected into limbic regions such as the BNST (Sahuque et al, 2006) or periaqueductal grey (Martins et al, 1997). However, very little is known about CRH receptor activation specifically in cortical regions and its effects on behavior.…”
Section: Experiments 2: Effect Of Crh Administration In the Mpfc On Anmentioning
confidence: 99%